Mental health: The new frontier for labour economics - Richard Layard (IZA Journal of Labor Policy, 2013)
This lecture argues that mental health is a major factor of production. It is the biggest single influence on life satisfaction, with mental health eight years earlier a more powerful explanatory factor than current income. Mental health also affects earnings and educational success. But, most strikingly, it affects employment and physical health. In advanced countries mental health problems are the main illness of working age - amounting to 40% of all illness under 65. They account for over one third of disability and absenteeism in advanced countries. They can also cause or exacerbate physical illness. It is estimated that in the absence of mental illness, the costs of physical healthcare for chronic diseases would be one third lower. The good news is that cost-effective treatments for the most common mental illnesses now exist (both drugs and psychological therapy). But only a quarter of those who suffer are in treatment. Yet psychological therapy, such as cognitive behavioural therapy, if more widely available would pay for itself in savings on benefits and lost taxes. The lecture ends by illustrating how rational policy can be made using life-course models of wellbeing. Such policies should include a much greater role for the treatment and prevention of mental illness.
Keywords: I30; J30; 330; Arbeitsproduktivität; Psychische Störung; Gesundheit; Zufriedenheit; Makroökonomischer Einfluss; Welt